SOLUBILITY OF PLATINUM IN AQUEOUS SOLUTIONS AT 25°C AND PHS 4 TO 10 UNDER OXIDIZING CONDITIONS - Azaroual M.; Romand B.; Freyssinet P.; Disnar J.R. (My University, 2001)
Platinum has been found to be mobile under supergene conditions, including placers and weathering profiles. To elucidate the nature of Pt mobility in supergene environments, the dissolution of platinum metal was investigated under physicochemical conditions similar to those found in such environments. The solubility of platinum metal was measured at 25°C in several systems: Pt-K-HC8H4O4-H2O (pH 4.02), Pt-Na-HCO3-Cl-H2O (pH 6.40), Pt-Na-K-H2PO4-HPO4-H2O (pH 6.90), Pt-Na-HCO3-H2O (pH 8.30), Pt-Na-OH-H2O (pH 8.54), and Pt-Na-HCO3-H2O (pH 9.91). The redox conditions of these experiments were relatively oxidizing, with measured Eh values ranging from +280 to +590 mV. The ionic strength of the aqueous solutions did not exceed 0.30 (molal scale).The interpretation of the solubility results, in terms of the following reaction and its equilibrium constant, Pt(s)+nH2O # Pt(OH)2-nn+nH++2e- served to identify the importance of the hydroxylated complex PtOH+ in the pH range (4 to 10) and to determine its stability constant at 25°C. Linear regression of the solubility data using the function log [Pt]-2pe=n pH+log Kn yielded a value of 1.01 +/- 0.07 for n, the average ligand number, and -31.76 +/- 0.55 for the thermodynamic equilibrium constant of reaction. The resulting stability constant (β1) of PtOH+ (Pt2+ + OH- # PtOH+) is 24.91 +/- 0.50, assuming the same value of the free energy of formation of Pt2+, ΔGf°(Pt2+) as that given by Glushko et al. (Thermodynamic Constants of Matter, Academy of Science, USSR, 1972). The range of values of ΔGf°(Pt2+) proposed to date is +185.63 to +258.74 kJ/mol. The value of Glushko et al. (1972) (+244.11 kJ/mol) appears to fit better with our measurements at pH 4 to 10 and with those of Wood (Wood S. A., ''Experimental determination of the hydrolysis constants of Pt2+ and Pd2+ at 25°C from the solubility of Pt and Pd in aqueous hydroxide solutions,'' Geochim. Cosmochim. Acta 55, 1759-1767, 1991) at pH 9 to 15.5. Finally, according to these new measurements of the solubility of platinum, the recommended values for Gibbs free energy (ΔGf°, in kiloJoule per mole) of the different aqueous species of Pt are +244.11 (Pt2+), -55.96 (PtOH+), and -234.48 (Pt(OH)2(aq)).The integration of data from the literature for chloride and sulfate complexes was used to calculate the speciation of platinum in seawater and in solutions with variable chlorinity (0.1, 1, and 3 mol/L NaCl) at 25°C. These calculations showed that in the absence of strong ligands (i.e., S2O32-, CN-), the transport of platinum in supergene environments primarily occurs in the form of PtOH+ (90%) and Pt(OH)2(aq) (9.7%). Chloride complexes (PtCl42- and PtCl3-) account for less than 1% of the dissolved platinum.This study clearly shows that the hydroxylated complexes (PtOH+ and Pt(OH)2(aq)) can play a very important role in controlling platinum transfer mechanisms in surface fluids (soils, placers, weathering profiles, etc.). Because the charged species PtOH+ is largely predominant, the mobility and transfer of platinum can also be affected by adsorption-desorption mechanisms onto oxides and hydroxides.